Themes and Tips for using “The Curious Incident of the Dog in the Night-Time” - Kansas State University, K-State First (My University, 2017)
This brochure provides ideas for faculty and staff at Kansas State University on the book “The Curious Incident of the Dog in the Night-Time” by Mark Haddon. Included on the brochure are themes, discussion questions, and activities. It also includes tips for using the book in a class, outside the classroom, and when planning events.
Citation: K-State Book Network (KSBN). (2017). Themes and Tips for using “The Curious Incident of the Dog in the Night-Time” [Brochures]. Manhattan, Kansas: K-State First.
Keywords: Curious Incident of the Dog in the Night-Time, The; Common reading program; Guide; Promotional materials